Use of Automatic Linear Modeling and Decision Trees in Body Weight Prediction in Normal Feathered Chickens (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
The aim of the study was to predict body weight (BWT) from linear body measurements of 200 mature normal feathered chickens, comprising 150 males and 50 females randomly selected in Amansea, Awka North LGA, Anambra State, Nigeria. Automatic Linear Modeling (ALM) and decision tree algorithms involving Chi-square Automatic Interaction Detector (CHAID), Exhaustive CHAID, and Classification and Regression Trees (CART) were used in the prediction. Adjusted coefficient of determination (R²adj.) and Alkaike’s Information Criterion corrected (AICc) were used to evaluate the predictive ability of ALM in males, females and pooled sexes. Males were significantly (p